District of Art - Performing Arts Events in Ringinanom Village, Kediri City, Indonesia: A Performance Studies Perspective - Aini, Desti Nur; Winarno, Agung; Wahyuni, Wiwik
Performing arts are a manifestation of the culture that exists in society which is reflected through behavior, and is learned through complex social interactions. Cultural uniqueness is a legacy of one of the areas in the city of Kediri, namely Ringinanom Village. Various art activists gathered and fused in an event performing arts and local culture so as to increase the spirit to be more creative in improving the existence of culture, especially in this region. However, the performing arts event titled District of Art (DoA) is still managed under conventional art management. Through this activity, DoA is developed and realized to be more modern and more collaborating with various art groups in this region in a single series through the process of creating art in an event. Activities that examine performing arts reveal other possible factors that have an impact on the existence of Ringinanom's distinctive art, namely from the aspect of the art creator, the aspect of performance, the aspect of the audience, and the aspect of management. A qualitative approach is carried out to produce a more extensive phenomenon. Data was collected using observation, documentation, and interviews. The data were analyzed using the 6P simultaneous stages proposed by Winarno and Robfiah, namely approach, excavation, deepening, matching, interpretation, and presentation. The results of the activity show that each of the existing art creators contributes positively to the overall role of the art group. From the aspect of the DoA performance, a systematic patterned process is carried out which is carried out before the show, during the show, and after the show. The views and influence of the public (audience) on DoA highlight the motivation of young artists who dare to work and perform through DoA's performing arts events. The management which was originally limited to incidental events turned into coordinated management and became a communication medium to inform local culture through an event. The results of this activity are expected to make DoA not only limited to art, but also the identity of the community that owns it.